An analysis of Hans J. Morgenthau's Politics among nations - Pardo, Ramon Pacheco (London : Macat International Limited, 2017)
"Hans Morgenthau';s Politics Among Nations is a classic of political science, built on the firm foundation of Morgenthau';s watertight reasoning skills.The central aim of reasoning is to construct a logical and persuasive argument that carefully organizes and supports its conclusions--often around a central concept or scheme of argumentation. Morgenthau';s subject was international relations--the way in which the world';s nations interact, and come into conflict or peace--a topic which was of vital importance during the unstable wake of the Second World War. To the complex problem of understanding the ways in which the post-war nations were jostling for power, Morgenthau brought a comprehensive schema: the concept of "realism"--or, in other words, the idea that every nation will act so as to maximise its own interests. From this basis, Morgenthau builds a systematic argument for a pragmatic approach to international relations in which nations seeking consensus should aim for a balance of power, grounding relations between states in understandings of how the interests of individual nations can be maximized.Though seismic shifts in international politics after the Cold War undeniably altered the landscape of international relations, Morgenthau';s dispassionate reasoning about the nature of our world remains influential to this day."--Provided by publisher.
chapter Ways in to the Text / Ramon Pacheco Pardo -- module 1 The Author and the Historical Context / Ramon Pacheco Pardo -- module 2 Academic Context / Ramon Pacheco Pardo -- module 3 The Problem / Ramon Pacheco Pardo -- module 4 The Author's Contribution / Ramon Pacheco Pardo -- section 1 Influences -- module 5 Main Ideas / Ramon Pacheco Pardo -- module 6 Secondary Ideas / Ramon Pacheco Pardo -- module 7 Achievement / Ramon Pacheco Pardo -- module 8 Place in the Author's Work / Ramon Pacheco Pardo -- section 2 Ideas -- module 9 The First Responses / Ramon Pacheco Pardo -- module 10 The Evolving Debate / Ramon Pacheco Pardo -- module 11 Impact and Influence Today / Ramon Pacheco Pardo -- module 12 Where Next? / Ramon Pacheco Pardo -- section 3 Impact.
Keywords: Morgenthau, Hans J -- 1904-1980. -- Criticism and interpretation; International relations